FENOMENA ‘BOSISME LOKAL’ DI ERA DESENTRALISASI: STUDI HEGEMONI POLITIK NUR ALAM DI SULAWESI TENGGARA - Eka Suaib; La Husen Zuada (Pusat Penelitian Politik, 2015)
This article discusses the emergence of Nur Alam as local bossism in Southeast Sulawesi. He started his career as an entrepreneur in the New Order era. Reform era and decentralization brought Nur Alam in political world by becoming the declarator of Amanat National Party (PAN) in Southeast Sulawesi, then lead the party and elected as a governor. After Nur Alam lead PAN in Southeast Sulawesi, this party has significant vote in the legislative elections in 2004, 2009 and 2014; was able to win the governor election in 2007 and 2012; and won 10 of 12 local election which took place in 2010 to 2013. During his leadership in Southeast Sulawesi, the economic growth was increased, the poverty rate was decreased, even the quality of physical infrastructure. His position as the leader of PAN as well as the governor in Southeast Sulawesi makes Nur Alam has big influence. He becomes stronger economically and more powerful politically because of his success in conquering his political opposition as well as his ability to collaborate with other local political elites. He also began to utilize the weakness of decentralization regulation by preparing his family as heir to the throne of his power. Keywords: local bossism, decentralization, Southeast Sulawesi.